2006
DOI: 10.1093/qjmed/hcl137
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid antibodies in Nigerian patients

Abstract: Thyroid autoimmunity appears more common in these Nigerian patients than in previous reports from Africa, and TPOAb was significantly associated with auto-immune thyroid disease. The clinical utility of these antibody measurements requires further evaluation in a wider African population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
2
13
2
Order By: Relevance
“…In this study, 80.6% patients were females. This compares with the study from Nigeria which found 77.9% of patients with thyroid disorders being females (6).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In this study, 80.6% patients were females. This compares with the study from Nigeria which found 77.9% of patients with thyroid disorders being females (6).…”
Section: Discussioncontrasting
confidence: 51%
“…As in this study, most of the patients in the study were in the 30 to 50 year age group. In a recent study among 104 patients with thyroid disorders in Nigeria, anti-TPOAbs were found in 60.5% of the patients (6).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…34 In the preiodization era, a typical case of HT was described as having scanty or absent colloid. Iodineinduced thyroiditis is known to be associated with residual goiter in endemic areas under iodine prophylaxis.…”
Section: Cytomorphologic Analysis Of Ht and Its Serologic Correlationmentioning
confidence: 99%
“…[11,12] Few studies have evaluated thyroid-antibody status in healthy African patients. [13][14][15][16][17][18] It is, however, known that thyroid-antibody levels decline progressively during pregnancy in healthy women without a thyroid disorder.…”
Section: Discussionmentioning
confidence: 99%